2018
DOI: 10.4038/sljas.v23i1.7546
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries enhancements in inland waters in Sri Lanka with special reference to culture based fisheries: current status and impacts

Abstract: Sri Lanka is endowed with more than 12,000 reservoirs. Depending on their hydrological regimes, they are broadly categorized into perennial and seasonal reservoirs and are secondarily used for the development of inland fisheries. This paper discusses the importance and status of culture-based fisheries (CBF) in reservoirs of Sri Lanka and assess the impacts of introduction of CBF. The CBF in seasonal reservoirs was initiated in the 1980s and it is well documented. There are around 200,000 ha of perennial reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…The study was unable to quantify the carrying capacity of GFWP in major and medium reservoirs, as most of the reservoirs were understocked and underutilized, which is clearly revealed by Figures 2 and 7. Though similar PRDs and RCEs for major and medium reservoirs were reported by Amarasinghe and Wijenayake (2015) and Chandrasoma and Pushpalatha (2018) at lower SDs than those applied in the current analysis, more comprehensive research is warranted before robust conclusions can be made. CBF practices of GFWP have been reported in Kerala, India (Nair et al., 2007) and Pak Mun dam (Run‐of‐River type reservoir) in Thailand (Sripatrprasite & Lin, 2003).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The study was unable to quantify the carrying capacity of GFWP in major and medium reservoirs, as most of the reservoirs were understocked and underutilized, which is clearly revealed by Figures 2 and 7. Though similar PRDs and RCEs for major and medium reservoirs were reported by Amarasinghe and Wijenayake (2015) and Chandrasoma and Pushpalatha (2018) at lower SDs than those applied in the current analysis, more comprehensive research is warranted before robust conclusions can be made. CBF practices of GFWP have been reported in Kerala, India (Nair et al., 2007) and Pak Mun dam (Run‐of‐River type reservoir) in Thailand (Sripatrprasite & Lin, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…The capacity of Sri Lankan reservoirs (Figure 1) to support the GFWP CBF is immense (Wijenayake et al., 2005). Regardless of the availability of a wide array of reservoirs (Amarasinghe & De Silva, 2016), supportive management frameworks (Wijenayake et al., 2021) and supplies of GFWP PLs (Chandrasoma & Pushpalatha, 2018), the production of GFWP is comparatively attenuated, unutilized and underestimated. It is a prerequisite to assess the adaptability and behavioural biology of riverine species, such as M. rosenbergii , when introduced to lacustrine systems, such as irrigation reservoirs (De Silva & Funge‐Smith, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aquaculture is the best fit for the changes surrounding Coastal-Vedda's SES, such as climate (e.g., cyclones, floods, and droughts) and way of life (e.g., non-mobile lifestyle). CBF can build more resilience among Coastal-Vedda than can other livelihoods, as it: (i) reduces food insecurity by supplying consistent protein sources (Amarasinghe and Nguyen, 2009), (ii) does not involve major investments (compared to intensive large-scale aquaculture operations), with the cost of fingerling stocking borne by multiple funders (RFO, NGOs, government) (Chandrasoma and Pushpalatha, 2018), and (iii) creates opportunities to collaborate and co-learn with external information/knowledge sources. Globally, aquaculture is identified as an adaptive strategy for climate change impacts and is included in some countries' national natural resources strategies (e.g., Solomon Islands, Vanuatu, Timor-Leste, Fiji, and Vietnam) (Bosma et al, 2012, Dey et al, 2016a, Dey et al, 2016b, Rosegrant et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Index of evenness was inverse to index of diversity so that the higher evenness was a temporary area. This opinion was supported by Wijenayake et al (2014); Chandrasoma and Pushpalatha (2018) that revealed the high index of diversity indicated that at this location it was feasible in terms of the availability of natural food for inland fisheries activities. On the other hand, temperature, sunlight, dissolved oxygen and pH were important components of plankton life and growth in various inundation.…”
Section: Discussionmentioning
confidence: 72%